Reformation today - Zamora García, Pedro (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Protestantism today is made up of a great diversity of organized churches and para-church groups institutionally separated from each other, being also characterized by an extreme theological plurality. During the last two centuries this diversity or plurality has been shaping a «denominational» reality that has been widely assumed both institutionally and theologically. That is to say that a large majority of Protestantism has assumed that the true Church is made up of a multitude of independent churches (denominations). This «denominationalism» could be one of the causes or, at least, of the instruments of its expansion, but it is currently subject to diverse types of rethinking or even of questioning, one of which has to do with the concern to recover a sense of catholicity. It is concluded in this work that the future of Evangelical Churches is that a good part of them delve theologically into catholicity and take steps towards an organizational structure of real unity.
Keywords: protestantism; denominacionalism; catholicity; church; ecumenism